2019
DOI: 10.3389/fneur.2019.00033
|View full text |Cite
|
Sign up to set email alerts
|

Functional Network-Based Statistics Reveal Abnormal Resting-State Functional Connectivity in Minimal Hepatic Encephalopathy

Abstract: Purpose: Whole-brain functional network analysis is an emerging methodology for exploring the mechanisms underlying hepatic encephalopathy (HE). This study aimed to identify the brain subnetwork that is significantly altered within the functional connectome in minimal HE (MHE), the earliest stage of HE.Materials and Methods: The study enrolled 19 cirrhotic patients with MHE and 19 controls who underwent the resting-state functional magnetic resonance imaging and cognitive assessment based on the Psychometric H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The operculum, adjacent to the insula, was responsible for sensory, motor, autonomic, and cognitive processing ( Maliia et al, 2018 ). The ROL was a major region involved in the language processing system, which played an important role in a variety of neurologic and psychiatric conditions ( Maliia et al, 2018 ; Shan et al, 2018 ; Zhan et al, 2019 ). The proximity of the anatomical structures may be the reason why they have a similar tendency to change in the progression of the AD spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The operculum, adjacent to the insula, was responsible for sensory, motor, autonomic, and cognitive processing ( Maliia et al, 2018 ). The ROL was a major region involved in the language processing system, which played an important role in a variety of neurologic and psychiatric conditions ( Maliia et al, 2018 ; Shan et al, 2018 ; Zhan et al, 2019 ). The proximity of the anatomical structures may be the reason why they have a similar tendency to change in the progression of the AD spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have found that Parkinson's disease (PD), Huntington's disease, schizophrenia, major depressive disorder, type 2 diabetes mellitus (T2DM), chronic obstructive pulmonary disease (COPD), lung cancer following chemotherapy, hepatic encephalopathy, kidney deficiency syndrome, and other diseases can also cause CI (70)(71)(72)(73)(74)(75)(76)(77)(78)(79), but the relationships between these diseases and cognitive function and the pathogenesis of CI are still unknown, necessitating further in-depth studies. rs-fMRI will play an important role in the exploration of these unknown areas.…”
Section: Application Of Rs-fmri In Mild Traumatic Brain Injury (Mtbi)mentioning
confidence: 99%
“…In order to investigate the FC strength within each subnetwork identified by NBS analysis, paired t-test was performed to compare the FC survived with NBS in the three conditions using SPSS version 25 (IBM Corp., Armonk, NY, United States). To correct for multiple comparisons, a false discovery rate (FDR) procedure was performed at q < 0.05 (Zhan et al, 2019). Following statistical analysis of the association between FC and physiological noise, multiple regression with interaction analysis was performed to compare slopes between rs-fMRI data that was Drif_NO, Drif_C, and Drif_CR in order to assess whether differential relationships exist between RR, PR, and z scores, with the z scores being the dependent variables in each regression model.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the FC strength within each subnetwork identified by NBS analysis, paired t -test was performed to compare the FC survived with NBS in the three conditions using SPSS version 25 (IBM Corp., Armonk, NY, United States). To correct for multiple comparisons, a false discovery rate (FDR) procedure was performed at q < 0.05 ( Zhan et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%